Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1073/pnas.1521156113
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of translation initiation complex formation by GE81112 unravels a 16S rRNA structural switch involved in P-site decoding

Abstract: In prokaryotic systems, the initiation phase of protein synthesis is governed by the presence of initiation factors that guide the transition of the small ribosomal subunit (30S) from an unlocked preinitiation complex (30S preIC) to a locked initiation complex (30SIC) upon the formation of a correct codon-anticodon interaction in the peptidyl (P) site. Biochemical and structural characterization of GE81112, a translational inhibitor specific for the initiation phase, indicates that the main mechanism of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 58 publications
(73 reference statements)
1
42
0
5
Order By: Relevance
“…Structural and kinetic analysis show that the engaged/disengaged state of the 30S subunit is also affected by the novel antibiotic GE81112, resulting in a blockade of the 30S IC progression by preventing initiation codon decoding [49]. Whether GE81112 perturbs the IF3 layout of the 30S subunit remains elusive; however, our model would suggest that the drug promotes a close distance conformation between domains.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and kinetic analysis show that the engaged/disengaged state of the 30S subunit is also affected by the novel antibiotic GE81112, resulting in a blockade of the 30S IC progression by preventing initiation codon decoding [49]. Whether GE81112 perturbs the IF3 layout of the 30S subunit remains elusive; however, our model would suggest that the drug promotes a close distance conformation between domains.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Die Gruppe der GE81112-Verbindungen, die von einer Streptomyces sp.p roduziert werden, stellt eine solche Klasse potenzieller neuer Leitstrukturen dar. [2,4] Die GE81112-Antibiotika sind unter Standard-Testbedingungen gegen E. coli nahezu inaktiv und entfalten ihre volle Aktivitätnur in Minimalmedien, da sie in die Bakterien durch das Oligopeptid-Permease-System (Opp) transportiert werden. [2,3] Die GE81112-Verbindungen hemmen die Proteinsynthese durch Wechselwirkung mit der kleinen 30S-ribosomalen Untereinheit.…”
unclassified
“…Antibacterial profiling has shown that each congener displays effective growth inhibition against several Gram‐positive and Gram‐negative pathogens . Recent studies indicated that GE81112 B stalls initiation in the unlocked 30S pre‐initiation complex state and impedes its transition to the corresponding initiation complex . This process represents a unique mechanism of action relative to other antibiotics that target the ribosome .…”
Section: Figurementioning
confidence: 99%